Laser Scissors and Tweezers to Study Chromosomes: A Review - Berns, Michael W. (Frontiers in Bioengineering and Biotechnology, 2020)
Starting in 1969 laser scissors have been used to study and manipulate chromosomes in mitotic animal cells. Key studies demonstrated that using the “hot spot” in the center of a focused Gaussian laser beam it was possible to delete the ribosomal genes (secondary constriction), and this deficiency was maintained in clonal daughter cells. It wasn’t until 2020 that it was demonstrated that cells with focal-point damaged chromosomes could replicate due to the cell’s DNA damage repair molecular machinery. A series of studies leading up to this conclusion involved using cells expressing different GFP DNA damage recognition and repair molecules. With the advent of optical tweezers in 1987, laser tweezers have been used to study the behavior and forces on chromosomes in mitotic and meiotic cells. The combination of laser scissors and tweezers were employed since 1991 to study various aspects of chromosome behavior during cell division. These studies involved holding chromosomes in an optical while gradually reducing the laser power until the chromosome recovered their movement toward the cell pole. It was determined in collaborative studies with Prof. Arthur Forer from York University, Toronto, Canada, cells from diverse group vertebrate and invertebrates, that forces necessary to move chromosomes to cell poles during cell division were between 2 and 17pN, orders of magnitude below the 700 pN generally found in the literature.